2016
DOI: 10.1111/cbdd.12831
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitroantileishmanial potential of peptide drug hirudin

Abstract: Hirudin is clinically an important drug used for the treatment of cardiac diseases, but has never been elucidated for antileishmanial potential. This study was designed to determine the therapeutic utility of hirudin against leishmaniasis. Binding affinities of 28 potent proteinase inhibitors were screened computationally against leishmanolysin (GP63), out of which hirudin exhibited higher binding affinity with GP63 and good expected IC values. Experimentally, hirudin showed most promising activity against pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…For compound 2, one hydrogen bond was formed with the benzene ring and Ala348 residue, and pi-alkyl interactions were also observed for the carbonyl oxygen and methyl group (-CH 2 ) with Ser449 and Ala349 residues, respectively. The molecular-level interactions that showed binding with the gp63 involved major hydrophobic protein residues, thus, a drug with more lipophilic groups could more easily bind to gp63 and effectively inhibit its activity [38] (Figure 4). SYTOX green assay was carried out to check membrane damage, and visualization under the fluorescence microscope confirmed that both compounds were responsible for damaging the cell membrane of Leishmania.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For compound 2, one hydrogen bond was formed with the benzene ring and Ala348 residue, and pi-alkyl interactions were also observed for the carbonyl oxygen and methyl group (-CH 2 ) with Ser449 and Ala349 residues, respectively. The molecular-level interactions that showed binding with the gp63 involved major hydrophobic protein residues, thus, a drug with more lipophilic groups could more easily bind to gp63 and effectively inhibit its activity [38] (Figure 4). SYTOX green assay was carried out to check membrane damage, and visualization under the fluorescence microscope confirmed that both compounds were responsible for damaging the cell membrane of Leishmania.…”
Section: Resultsmentioning
confidence: 99%
“…Acridine orange assays are used to characterize different stages of apoptosis in cells and to check for DNA damage. Acridine orange dye can insert into DNA and emits green fluorescence when bound to normal DNA or dsDNA, and red fluorescence when bound to damaged or ssDNA [38]. For both compounds, early apoptotic (EA) cells started appearing at 12 h and increased along with the treatment time, whereas late apoptotic (LA) cells were observed after 48 h of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No caso do tempo de 16 h, foram observados resultados de inibição muito próximos daqueles observados para 24 h. principais moléculas de superfície em promastigotas de Leishmania. 94 Interessantemente, a GP63 é uma metaloprotease Zn-dependente com importante papel na virulência parasitária que poderia ser alvo dos compostos de Au I , já que possuem alta afinidade pelo sítio de ligação do zinco.…”
Section: Viabilidade Dos Promastigotasunclassified